Hidden Influence of School Principals in Developing School Culture to Strengthen Educational Quality - Falakhunnisa Falakhunnisa; Imron Imron (The Future of Education Journal, 2026)
Educational quality improvement is not only determined by the managerial and administrative capabilities of school principals but also by their ability to develop school culture through social influence that is not always formally visible. Previous studies on principal leadership have predominantly focused on formal leadership approaches, while the concept of hidden influence remains underexplored in educational research. This study aims to examine the concept, forms, and roles of principals’ hidden influence in developing school culture to strengthen educational quality. This study employed a qualitative approach using a library research method. Data were collected from scientific journals, books, academic articles, and previous studies relevant to the research topic. Documentation techniques were used for data collection, while data were analyzed through content analysis and literature synthesis. The findings reveal that principals’ hidden influence plays a significant role in shaping school culture and enhancing educational quality. This influence is reflected in six main dimensions: role modeling, interpersonal communication, emotional approaches, habituation of positive culture, informal motivation, and the creation of a conducive school climate. These dimensions contribute to the development of a disciplined and collaborative school culture, the strengthening of students’ character, and increased teacher work motivation. The study concludes that the successful development of school culture and educational quality is influenced not only by formal leadership practices but also by principals’ ability to build sustainable social, emotional, and cultural influence. This research offers a conceptual model of hidden influence as a new perspective in educational leadership studies.